Quartz sand proppant loaded with Ni and Mo for in-situ aquathermolysis of heavy oil. (15th December 2021) - Wang, Jianwei; Tang, Xiaodong; Li, Jingjing; Guo, Erpeng; Guan, Wenlong; Jiang, Youwei
Highlights: The aquathermolysis catalyst was prepared directly with quartz sand proppant as a carrier by impregnation method. In-situ catalytic upgrading of heavy oil was simulated by heavy oil thermal recovery multifunctional model experiment device. Asphaltene single molecules and asphaltene aggregates are the main factors affecting the viscosity of crude oil. X-ray photoelectron spectroscopy (XPS) indicate the presence of a variety of Ni and Mo species on the quartz sand proppant surface, including NiO, NiOOH, MoO2, and MoO3, which promote the aquathermolysis. Abstract: The aquathermolysis is an emerging technology that can realize the in-situ upgrade and viscosity reduction of heavy oil in the reservoir conditions. In this study, a heterogeneous catalyst: Ni-Mo/SiO2 was prepared by the impregnation-calcination method and quartz sand proppant (SiO2 : 20–40 mesh) was used as the carrier. Through the catalytic aquathermolysis of Liaohe heavy oil, the catalytic performance of the catalyst was explored. Under the set conditions (240 °C, 24 h, 50% water content), 16.21% of the heavy components (6.92% resins and 9.29% asphaltenes) can be converted to light components. The large-particle quartz sand proppant as the carrier can realize the separation of Ni-Mo from the oil–water mixture, effectively avoiding the loss. After 5 cycles, Ni-Mo/SiO2 can still maintain a viscosity reduction rate of more than 72%. The viscosity of Liaohe heavy oil decreased from 145 Pa·s to 23.26 Pa·s in the simulated in-situ upgrading experiment, which indicated the feasibility of Ni-Mo/SiO2 to in-situ modification of heavy oil.